UNO DMRG CASCI calculations of effective exchange integrals for m-phenylene-bis-methylene spin clusters. (17th September 2017) - Kawakami, Takashi; Sano, Shinsuke; Saito, Toru; Sharma, Sandeep; Shoji, Mitsuo; Yamada, Satoru; Takano, Yu; Yamanaka, Shusuke; Okumura, Mitsutaka; Nakajima, Takahito; Yamaguchi, Kizashi
ABSTRACT: Theoretical examinations of the ferromagnetic coupling in the m -phenylene-bis-methylene molecule and its oligomer were carried out. These systems are good candidates for exchange-coupled systems to investigate strong electronic correlations. We studied effective exchange integrals ( J ), which indicated magnetic coupling between interacting spins in these species. First, theoretical calculations based on a broken-symmetry single-reference procedure, i.e. the UHF, UMP2, UMP4, UCCSD(T) and UB3LYP methods, were carried out with a GAUSSIAN program code under an SR wave function. From these results, the J value by the UHF method was largely positive because of the strong ferromagnetic spin polarisation effect. The J value by the UCCSD(T) and UB3LYP methods improved an overestimation problem by correcting the dynamical electronic correlation. Next, magnetic coupling among these spins was studied using the CAS-based method of the symmetry-adapted multireference methods procedure. Thus, the UNO DMRG CASCI (UNO, unrestricted natural orbital; DMRG, density matrix renormalised group; CASCI, complete active space configuration interaction) method was mainly employed with a combination of ORCA and BLOCK program codes. DMRG CASCI calculations in valence electron counting, which included all orbitals to full valence CI, provided the most reliable result, and support the UB3LYP method for extended systems. Abstract :